STUDENT DIFFICULTIES IN ENGLISH LEARNING DURING LIMITED PTM PERIOD - Muhtarom Muhtarom; Azizatul Maghfiroh (International Journal of Research on English Teaching and Applied Linguistics, 2022)
As an international language, English is important in globalization era and therefore taught in secondary schools, including MTs as one of the Islamic ones. However, the students of this Islamic school might feel bored and even they avoid of having English. And, therefore, this study is to describe students' difficulties in learning English during limited offline Teaching Learning Process (PTM) Period and to describe the factors that cause learning difficulties in English during limited PTM Period. Then, the method used in this study is a descriptive research design. The subjects in this study were 33 students who are all in class IX-A MTsN Gresik for the academic year 2021/2022. Data collection techniques used in thisstudy were interviews, questionnaires and documentation, then the analysis used is a qualitative approach. Based on the analysis, the results are that there are two factors that affect the difficulty of learning English for students of class IXA MTsN Gresik, that are internal factors and external ones. The internal ones includes less motivation and interest in attending English lesson, while the external ones consist of the less attractive medias and the less various and innovative methods. Based on the results above, it can be concluded that, first, the students of class IX-A MTsN Gresik still have difficulty in learning English lessons, because of internal and external factors.